Low-dose ATG/PTCy for graft-versus-host disease prevention in haploidentical transplantation: a single-center experience - Hong, Jian; Liang, Xinglin; Ni, Jing; Ruan, Min; Long, Zhangbiao; Dai, Jifei; Liang, Li; Yang, Mingya; Zhang, Ziyang; Zhang, Shihao; Ge, Jian; Yang, Mingzhen; et al. (Frontiers in Oncology, 2025)
BackgroundThe combination of anti-thymocyte globulin (ATG) and post-transplant cyclophosphamide (PTCy) has been administered for graft-versus-host disease (GVHD) prophylaxis of haploidentical hematopoietic stem cell transplantation (haplo-HSCT) in recent years. Varied doses of ATG and PTCy were applied in multiple studies with promising outcomes.MethodsWe retrospectively analyzed 51 consecutive leukemia patients who underwent haplo-HSCT with the joint use of low-dose ATG (27 patients with 7.5 mg/Kg and 24 patients with 5 mg/Kg) and PTCy (29 mg/Kg) for GVHD prophylaxis in our center. The impact of different ATG doses and absolute lymphocyte count (ALC) before ATG infusion was also evaluated.ResultsThe 100-day cumulative incidences (CIs) of grade I-IV, II-IV and III-IV acute GVHD of the whole cohort were 42.9%, 34.7% and 12.2%, respectively. The 2-year CIs of overall and moderate-to-severe chronic GVHD were 44.7% and 27.7%, respectively. The 2-year overall survival, disease-free survival, non-relapse mortality and CI of relapse were 66.7%, 54.8%, 25.5% and 19.7%, respectively. Between 7.5 and 5 mg/Kg ATG groups, no significant difference on CIs of acute GVHD was observed. Interestingly, pre-ATG ALC impacted the occurrence of acute GVHD. With a cutoff point of 0.585×109/L, low ALC group showed reduced CIs of grade I-IV (16.7% versus 58.0%, p=0.01), II-IV (16.7% versus 45.1%, p=0.06) and III-IV (0 versus 19.4%, p=0.05) acute GVHD as compared to high ALC group.ConclusionsThe results suggested that this low-dose ATG/PTCy regimen was feasible and pre-ATG ALC levels could influence the occurrence of acute GVHD in this regimen.